2014
DOI: 10.2131/jts.39.147
|View full text |Cite
|
Sign up to set email alerts
|

Development of LLNA:DAE: a new local lymph node assay that includes the elicitation phase, discriminates borderline-positive chemicals, and is useful for cross-sensitization testing

Abstract: -We developed a new local lymph node assay (LLNA) that includes the elicitation phase termed LLNA:DAE for discrimination of borderline-positive chemicals as classified by the LLNA modified by Daicel based on ATP content (LLNA:DA) and for cross-sensitization testing. Although the LLNA:DA method could help identify skin sensitizers, some skin irritants classified as non-sensitizers by the LLNA were classified as borderline positive. In addition, the evaluation for the cross-sensitization potential between chemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…This result was obtained in a mouse treated with 0.06% DNCB. This weight (2.7 mg) was similar to the lymph node weight of naïve mice (Yamashita et al, 2014). Therefore, we concluded that this dose of (0.06% DNCB) was not suitable as the test dose for the primary LLNA:DAE study, due to the possibility of a false negative result from the variability in lymph node weights between mice.…”
Section: Discussionmentioning
confidence: 78%
See 4 more Smart Citations
“…This result was obtained in a mouse treated with 0.06% DNCB. This weight (2.7 mg) was similar to the lymph node weight of naïve mice (Yamashita et al, 2014). Therefore, we concluded that this dose of (0.06% DNCB) was not suitable as the test dose for the primary LLNA:DAE study, due to the possibility of a false negative result from the variability in lymph node weights between mice.…”
Section: Discussionmentioning
confidence: 78%
“…The test dose selected for the validation study was the dose that gave the highest left ear lymph node weight or the dose that gave a left ear lymph node weight of at least 4 mg. For glycerol and sulfanilamide, the left ear lymph node weights obtained from all dose groups were in the same range as the lymph node weights of naïve mice; therefore, the highest concentrations were selected. The lymph node weights for naïve mice were reported in our previous study (Yamashita et al, 2014). When 1.56% glutaraldehyde, 6.25% propyl gallate, 25.0% resorcinol, 25% NiSO 4 , 12.5% cinnamic aldehyde, 25.0% abietic acid, and 50.0% hydroxycitronellal were tested, a clear elicitation response was observed.…”
Section: Validation Of Llna:dae Methods As a Stand-alone Skin Sensitizmentioning
confidence: 82%
See 3 more Smart Citations